EFFECTS OF SHUMIANNING ON ANESTHESIA, RESPIRATION AND CIRCULATION IN DOGS - L. Guo; Y. Yu; J. Sun; J. Lu; S. Yu; G. Xu (Journal of Animal and Plant Sciences, 2019)
The present experiment was conducted to study the effects of Shumianning, a compound anesthetic, on the effects of anesthesia as well as respiration and circulation in dogs. Ten adult healthy mongrel dogs were selected, with an equal number of male and female dogs, weighing about 8~10 kg. No. 24 indwelling intravenous catheter was put into the left forelimb (cephalic vein) to create venous tunnel. Shumianning at a dosage of 0.05 mL/kg was intravenously injected at first, and then continuous intravenous infusion was conducted by micropump for 1 hour with the speed of 0.1 mL/kg/hr. 10 min after the injection, heart rate (HR), respiratory rate (RR), mean systolic arterial pressure (SAP), diastolic arterial pressure (DAP), partial pressure of oxygen (PO2) and arterial oxygen saturation (SpO2) were measured to evaluate the effects of sedation and recovery. Anesthesia mean onset time was (26.8 ±10.5) min, mean maintenance time was (89.6±17.5) min and mean recovery time was (15.6±5.8) min. There were no differences in the scores of sedation, analgesia and muscle relaxation as well as anesthetic effects at 20, 30 and 60 minutes (p>0.05). Finally, there were 7 dogs (70.0%) with excellent recovery, 2 (20.0%) with good recovery and 1 (10.0%) with an average quality of recovery. Shumianning exerts high effect upon the induction, maintenance and recovery of dog models receiving intravenous general anesthesia.
Keywords: Shuumianning; intravenous general anesthesia; micropump; induction period; maintenance period; recovery period